recruitment and selection on developing the The impact of manpower performance of business organization: ( 2018-2020 Case study Kenana Sugar Company) - فريد حسن بيومي; د/ميادةمحمد; مرتضى محمود برير (White Nile Journal for Studies and Research, 2021)
The research aims to identify the different concepts of recruitment and selecting the workforce and their role in the development of the company's human capital performance and development of the company itself, Then studying the relationship between the recruitment and selection of the workforce and development of the company's performance, as the problem of the study lies in the low rate of growth and development of the company's business in addition to its profitability. As a large percentage of its workforce, which includes different competencies and skills, has decreased. The company spent large sums on it through recruitment, selection and processes. Kenana Sugar Company was taken as a sample for the study, where appropriate statistical methods were used by building a questionnaire and it was distributed to the community sample of (1) After conducting statistical analyzes using the (SPSS) program, the study reached a set of results, including the existence of a statistically significant relationship between choosing the workforce and developing the performance of the Kenana Sugar Company. There is a statistically significant relationship between owning and creating a qualified cumulative human balance and the extent to which the loss of the workforce at Kenana Sugar Company is reduced. As for the recommendations made by the research, it is to pay attention to the principles of sound recruitment before conducting the selection processes selecting the appropriate Human resources in the recruitment processes, and the appropriate persons must be selected and recruited. To fill positions according to the qualifications required in the job description.